I am teaching a student in a course without partial differentiation so(adsbygoogle = window.adsbygoogle || []).push({});

I can only think of the following method

let b be a constant and set y=b so

xb= exp(x-1) +blnb

means b= exp(x-1) which means x = lnb+1

now d(xb)/dx= b

and d(exp(x-1)+blnb)/dx = exp(x-1)

so if x > lnb+1

xb> exp(x-1) + blnb

since the Right hand side has a higher derivative

so x > lnb+1 Implies xb> exp(x-1) + blnb

so

x > lny +1 implies xy< exp(x-1) + ylny

Now replace x with b

by = exp(b-1) + ylny

means

y=exp(b-1)

now d(by)/dx= b

and d( exp(b-1) + ylny)/dx = 1+ lny

so if lny+ 1 > b

by < exp(b-1) + ylny

since the derivative of the right hand is larger

so lny+1 >x implies xy < exp(x-1)+ylny

**Physics Forums - The Fusion of Science and Community**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# How to prove xy <= exp(x-1) +ylny using differentiation

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

Loading...

Similar Threads for prove +ylny using | Date |
---|---|

I Minimization using Lagrange multipliers | Saturday at 7:28 PM |

I Proving the Linear Transformation definition | Mar 27, 2018 |

I A problematic limit to prove | Jan 26, 2018 |

I Proving equivalence between statements about a sequence | Feb 12, 2017 |

I Prove that ∫f(x)δ(x)dx=f(0) | Jan 22, 2017 |

**Physics Forums - The Fusion of Science and Community**